Animal carcass processing, cooking and consumption at Early Neolithic Revenia-Korinou, northern Greece. (10th December 2018) - Isaakidou, Valasia; Halstead, Paul; Adaktylou, Foteini
Abstract: The open-air settlement of Revenia-Korinou has yielded the largest Early Neolithic (7th millennium BC) faunal assemblage to date from Greece. The assemblage, recovered from numerous pits, is heavily dominated by domestic sheep, goats, pigs and cattle. Here we focus on the evidence for butchery and consumption of animals, to explore how carcass products were cooked (in the absence of cooking pots) and what if any role they played in commensal politics. Evidence for dismembering and filleting is sparse, implying butchery of domestic animal carcasses into large segments (including more or less complete limbs) for cooking, apparently in ovens or pits rather than on open fires. Subsequently limb bones were intensively smashed to extract marrow and probably grease, perhaps by boiling in organic containers. Dismembering, filleting and marrow extraction were most intensive for cattle, but bone grease was more systematically exploited in the case of sheep/goats, implying differences between taxa in contexts of consumption. Significant differences between pits in taxonomic composition and the incidence of gnawing and burning suggest that each represents short-term and/or localized discard, perhaps by a small residential group. Within individual pits, matching unfused diaphyses and epiphyses and joins between fragments broken in antiquity confirm rapid burial, but bones separated by dismembering seem to have been dispersed across the settlement before discard. The distribution of carcass products, both cooked and uncooked, played a role in shaping relationships between small residential units and the wider community at Early Neolithic Revenia-Korinou.